Lysine and arginine reduce the effects of cerebral ischemic insults and inhibit glutamate-induced neuronal activity in rats - Kondoh, Takashi; Kameishi, Makiko; Mallick, Hruda N.; Ono, Taketoshi; Torii, Kunio (Frontiers in Integrative Neuroscience, 2010)
Intravenous administration of arginine was shown to be protective against cerebral ischemic insults via nitric oxide production and possibly via additional mechanisms. The present study aimed at evaluating the neuroprotective effects of oral administration of lysine (a basic amino acid), arginine, and their combination on ischemic insults (cerebral edema and infarction) and hemispheric brain swelling induced by transient middle cerebral artery occlusion/reperfusion in rats. Magnetic resonance imaging and 2,3,5-triphenyltetrazolium chloride staining were performed two days after ischemia induction. In control animals, the major edematous areas were observed in the cerebral cortex and striatum. The volumes associated with cortical edema were significantly reduced by lysine (2.0 g/kg), arginine (0.6 g/kg), or their combined administration (0.6 g/kg each). Protective effects of these amino acids on infarction were comparable to the inhibitory effects on edema formation. Interestingly, these amino acids, even at low dose (0.6 g/kg), were effective to reduce hemispheric brain swelling. Additionally, the effects of in vivo microiontophoretic (juxtaneuronal) applications of these amino acids on glutamate-evoked neuronal activity in the ventromedial hypothalamus were investigated in awake rats. Glutamate-induced neuronal activity was robustly inhibited by microiontophoretic applications of lysine or arginine onto neuronal membranes. Taken together, our results demonstrate the neuroprotective effects of oral ingestion of lysine and arginine against ischemic insults (cerebral edema and infarction), especially in the cerebral cortex, and suggest that suppression of glutamate-induced neuronal activity might be the primary mechanism associated with these neuroprotective effects.